3, 5-Dimethoxy-4-hydroxy myricanol ameliorates photoreceptor cell degeneration in Pde6brd10 mouse model. (2nd January 2019) - Wang, Yan-Yan; Wang, Chen-Guang; Qi, Shou-Nan; Liu, Zao-Xia; Su, Guan-Fang; Zheng, Ya-Juan
Abstract: Introduction: Retinitis pigmentosa (RP) caused by the photoreceptor cell degeneration is currently incurable and leads to partial or complete blindness eventually. 3, 5-dimethoxy-4-hydroxy myricanol (DM) is a novel compound isolated from the leaves of Micromelum integerrimum, with proliferative activities on NIH3T3 cells. This study was to investigate whether DM could mitigate retinal degeneration of rd10 mice, a well-characterized mouse model of RP. Materials and method: Rd10 mice were treated with DM daily by intraperitoneal injection from postnatal day 12 (P12) to P26. Electroretinography (ERG) reflects the mass response of photoreceptor cells and was used to test the outer retinal function after DM treatment. Haematoxylin and Eosin staining was used to show the retinal morphology and evaluate the rod photoreceptor cell loss. TUNEL assay was used to detect the apoptosis-positive cells. Inflammatory factors were measured by ELISA to show the inflammatory response. Real-time PCR and western blot were applied to measure the gene and protein change to explore the underlying mechanisms. Results: Results showed that DM significantly improved the retinal function by increasing the ERG amplitude, preserving the retinal morphology, reducing photoreceptor cell apoptosis, decreasing inflammatory response, and inhibiting endoplasmic reticulum stress in rd10 mice. Conclusion: This is the first time when the protective effects of DM against photoreceptor cell degeneration of rd10 mice have been demonstrated, providing scientific rationale to develop DM as a potential agent to treat RP.